CHARACTER EDUCATION AS THE PRIMARY PURPOSE OF SCHOOLING FOR THE FUTURE - Lewis, McRobert; Ponzio, Veronica (SCAD Independent, 2016)
This analysis seeks to examine the history and development of moral/character education in America during the 20th century providing structure for the character education movement in today’s educational context. The common denominator and key to character education for the future is community. The concept of community connects the three aforementioned themes and provides a roadmap for better implementation of character education. Careful consideration is given to the interaction and contributions of the school and society in terms of promoting and developing character education. Though there is generous support from politicians, educators, and parents, character education is still somewhat mired by its lack of scope. This examination proposes that current character education proponents can find new frameworks for implementation by observing the history of character education.